POLA NAMA DESA DI KABUPATEN PONOROGO PADA ERA ADIPATI RADEN BATORO KATONG: SEBUAH TINJAUAN ETNOLINGUISTIK - Alip Sugianto (Institut Teknologi Sepuluh Nopember, 2017)
This paper expplains that the Pattern Name of villages in Ponorogo at period of Duke Raden Katong Batoro has some morphological word formations and meanings. For the method, this research used literature and historical analysis. Research shows that names of the village in Ponorogo relate to Batoro Katong. From the historical point of view, names of the villages came from the names of People Punggawa Raden Batoro Katong who have lived in and founded Ponorogo. This was intended for the remembrance of Raden Katong Batoro’s struggle, the founding father of Ponorogo.